Effectiveness of the Hidden Curriculum on Affective Attitudes of High School Students Toward Learning - Yaghoob Raissi Ahvan; Ali Akbar Shaykhei Fini; Hossein Zainalipour (Gonabad University of Medical Sciences, 2021)
Background: The effectiveness of the hidden curriculum is stronger than the explicit curriculum from the perspectives of curriculum experts and medical education specialists. These effects are especially strong in transmitting values, norms, and medical professionalism. So, the importance of the hidden curriculum and its impact on educating medical students is undeniable. The present study aimed to explore the effect of the hidden curriculum components on affective attitudes of students toward learning, and to create a better learning and educational setting. Methods: The research was a mixed-method using a cross-sectional survey in the quantitative section. A case study (phenomenological analysis of lived experience type) and the interviews were used in the qualitative part. The study population consisted of 277 male high school students in District 1 of Bandar Abbas Port, Iran, in the 2019-2020 academic year. They were selected through the cluster sampling method and randomly assigned to the experimental research. Results: The results of multiple regression analysis showed a correlation (0.627) between the components of the hidden curriculum with affective attitudes of learning (P<0.95). The quantitative findings showed the mean scores of most components in exceptional talents (SAMPAD) high school students were significantly higher than the mean scores in public and non-public high schools students (P<0.05). Moreover, the results of the path analysis showed that the hidden curriculum has a positive and significant relationship with the three components of affective attitudes of students toward learning.. Conclusion: Generally, the hidden curriculum plays a vital role through the implicit transfer of values, attitudes, and skills to students, especially on affective attitudes, so that these issues should receive more attention by the educators in every educational setting.